The involvement of microRNAs in Type 2 diabetes. (24th November 2010) - Ferland-McCollough, David; Ozanne, Susan E.; Siddle, Kenneth; Willis, Anne E.; Bushell, Martin
Abstract : T2D (Type 2 diabetes mellitus) is a major health issue that has reached epidemic status worldwide. T2D is a progressive metabolic disorder characterized by reduced insulin sensitivity, insulin resistance and pancreatic β-cell dysfunction. Improper treatment of TD2 can lead to severe complications such as heart disease, stroke, kidney failure, blindness and nerve damage. The aetiology and molecular mechanisms of T2D are not fully understood, but compelling evidence points to a link between T2D, obesity, dyslipidaemia and insulin resistance. Although T2D seems to be strongly linked to environmental factors such as nutrition and lifestyle, studies have shown that genetic factors, such as polymorphisms associated with metabolic genes, imprinting, fetal programming and miRNA (microRNA) expression, could also contribute to the development of this disease. miRNAs are small 22–25-nt-long untranslated RNAs that negatively regulate the translation of mRNAs. miRNAs are involved in a large number of biological functions such as development, metabolism, immunity and diseases such as cancer, cardiovascular diseases and diabetes. The present review examines the various miRNAs that have been identified as being potentially involved in T2D, focusing on the insulin-sensitive organs: white adipose tissue, liver, skeletal muscle and the insulin-producing pancreatic β-cells.